Pemikiran Tauhid Âyât Allâh Murtadâ Mutahharî - Safii, Safii (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This article explores the ideas of Murtadâ Mutahharî, Shî?ah thinkers, about his thoughts of tawheed. By using the analytical methods of genealogical and critical, this article concludes that the thought of Mutahharî besides not entirely the same as the Mu?tazilah who deny the existence of God?s attributes in addition to his substance, is also not in line with Ash?arîyah who believes in the existence properties separate God beside his substance, but between the two completely fused integrally. It shows that he is not completely unaffected by the Mu?tazilah and Ash?arîyah. Similarly, the act of thinking about tawheed (tawhid fî al-Af?âl), where he was influenced by Ash?arîyah, although the effect is not as big as the levels derived from Mu?tazilah.